2013
DOI: 10.1111/jam.12274
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection effectiveness of slightly acidic electrolysed water in swine barns

Abstract: Aims: To evaluate the disinfection effectiveness of slightly acidic electrolysed water (SAEW, pH 6Á25-6Á53), a new environmental friendly agent for inactivating micro-organisms adhered to the facility and aerosolized in the air of the swine barns and to explore the application of SAEW in livestock industries. Methods and Results: Bacteria and fungi were isolated from the swine house air and treated by SAEW. The SAEW solution was flushed onto surfaces and sprayed within the whole swine barn. SAEW with an availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 34 publications
(59 reference statements)
1
36
0
1
Order By: Relevance
“…and E. coli by 21% and 16%, respectively. Hao and others () also reported on the potential applications of SAEW in swine barns. SAEW containing 300 ppm of active chlorine was flushed onto surfaces and sprayed within the whole swine barn.…”
Section: Applications Of Ewmentioning
confidence: 99%
“…and E. coli by 21% and 16%, respectively. Hao and others () also reported on the potential applications of SAEW in swine barns. SAEW containing 300 ppm of active chlorine was flushed onto surfaces and sprayed within the whole swine barn.…”
Section: Applications Of Ewmentioning
confidence: 99%
“…The microbicidal effect of HOCl solution has been well studied Kim et al, 2008, Hao et al, 2013 . This reagent has broad-spectrum microbicidal activity.…”
mentioning
confidence: 99%
“…To date, different sanitizers like hypochlorites, organic acids, and ozone [5,6] have been employed to disinfect fresh produce. Electrolyzed water produced by the electrolysis of a dilute salt (NaCl) or hydrogen chloride (HCl) solution has been reported to exhibit a broad spectrum of antimicrobial activity [7,8]. Slightly acidic electrolyzed water (pH of 5.0-6.5) is regarded as one of the most promising sanitizers as it is generally recognized as safe (GRAS).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have been reported for using high concentrations of slightly acidic electrolyzed water [7,11]. However, limited scientific studies have been involved in process development and understand the properties of electrolyzed water at different conditions.…”
Section: Introductionmentioning
confidence: 99%